2009
DOI: 10.1590/s1809-29502009000200010
|View full text |Cite
|
Sign up to set email alerts
|

Estimulação elétrica nervosa transcutânea nas modalidades convencional e acupuntura na dor induzida pelo frio

Abstract: ACEITO PARA PUBLICAÇÃO maio 2009RESUMO: A estimulação elétrica nervosa transcutânea (TENS) é um recurso não-farmacológico já consagrado na modulação de dores agudas e crônicas. O objetivo deste estudo foi verificar o efeito da TENS convencional e na modalidade TENSacupuntura na dor induzida pelo frio. Trinta indivíduos saudáveis com idade entre 18 e 40 anos foram distribuídos ao acaso em três grupos: placebo, TENS convencional e TENS-acupuntura. Foi utilizado um protocolo de indução de dor pelo frio composto p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
1
2
0
7
Order By: Relevance
“…Although TENS is effective in treating acute pain, in this study this fact was not observed, regardless of the frequency used: neither 7Hz, 100Hz, nor 255Hz was effective in increasing the pain threshold induced by pressure in the hypothenar region in our evaluations, which is in agreement with the results obtained by Schulz et al ( 4 ) on the action of TENS in the form of Burst on the threshold of pain induced by pressure. This study also did not display differences of pain caused by cold (superficial), similar to what was found by Morimoto et al ( 8 ) when stimulating with 80Hz or 4Hz. On the other hand, Montenegro et al, ( 1 ) when stimulating with TENS at acupuncture points, did not observe effects on the intensity of pain, but there was an increase in pain threshold to cold, a fact also observed by Santos et al ( 13 )…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Although TENS is effective in treating acute pain, in this study this fact was not observed, regardless of the frequency used: neither 7Hz, 100Hz, nor 255Hz was effective in increasing the pain threshold induced by pressure in the hypothenar region in our evaluations, which is in agreement with the results obtained by Schulz et al ( 4 ) on the action of TENS in the form of Burst on the threshold of pain induced by pressure. This study also did not display differences of pain caused by cold (superficial), similar to what was found by Morimoto et al ( 8 ) when stimulating with 80Hz or 4Hz. On the other hand, Montenegro et al, ( 1 ) when stimulating with TENS at acupuncture points, did not observe effects on the intensity of pain, but there was an increase in pain threshold to cold, a fact also observed by Santos et al ( 13 )…”
Section: Discussionsupporting
confidence: 92%
“…A care taken in the present study was standardization of the initial temperature, before the first evaluation. In a study conducted by Morimoto et al, ( 8 ) before each assessment, the member evaluated was immersed in warm water so that the temperature was uniform in each one of the evaluations. Such care not taken in the present study may have caused alterations in the thresholds of pain detected.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations